Gas exchanges and mineral content of corn crops irrigated with saline water - dos Santos Rodrigues, Valdécio; Gomes de Sousa, Geocleber; da Costa Soares, Stallone; Nascimento Leite, Kelly; D'´Araújo Ribeiro de Ceita, Emanuel; Machado de Sousa, José Thomas (Revista Ceres, 2025)
Inferior quality water can be used by agricultural producers in arid and semi-arid regions due to the lower availability of good-quality water. Therefore, the objective was to identify the influence of irrigation with saline water on gas exchange and leaf contents in corn (Zea mays L.) crop. The work was conducted in the field, in the experimental area of the Experimental Farm of the University of International Integration of Afro-Brazilian Lusofonia (UNILAB), RedençãoCE. The experimental design used in the research was randomized blocks, with five treatments: 1.0; 2.0; 3.0; 4.0 and 5.0 dS m-1 and four repetitions. At 45 days after sowing (DAS) the gas exchange variables were evaluated: transpiration, stomatal conductance, photosynthesis, internal CO2 concentration, water use efficiency and leaf temperature. And at 110 DAS the contents of N, P, K, Ca and Mg in plant leaves. The saline stress due to saltwater irrigation leads to a reduction in photosynthesis, stomatal conductance, internal CO2 concentration and transpiration in field maize plants. Salt stress reduces the levels of N, P, K, Ca and Mg mineral elements in maize leaves.